2016 International Conference on Smart Systems and Technologies (SST) 2016
DOI: 10.1109/sst.2016.7765637
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of variable Smart Grid traffic over ad hoc Wireless Mesh Networks

Abstract: Abstract-Recent advances in ad hoc Wireless Mesh Networks (WMN) has posited it as a strong candidate in Smart Grid's Neighbourhood Area Network (NAN) for Advanced Metering Infrastructure (AMI). However, its abysmal capacity and poor multi-hoping performance in harsh dynamic environment will require an improvement to its protocol stacks in order for it to effectively support the variable requirements of application traffic in Smart Grid. This paper presents a classification of Smart Grid traffics and examines t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…In CSMA/CA based wireless environments, broadcast transmissions may induce potential problems such as data congestion and packet collision due to shared medium characteristics [16].…”
Section: Efficient Ccn Packet Dissemination By Mpr Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…In CSMA/CA based wireless environments, broadcast transmissions may induce potential problems such as data congestion and packet collision due to shared medium characteristics [16].…”
Section: Efficient Ccn Packet Dissemination By Mpr Devicesmentioning
confidence: 99%
“…In CSMA/CA based wireless environments, broadcast transmissions may induce potential problems such as data congestion and packet collision due to shared medium characteristics [16]. However, CCN only considers the broadcasting approach to transmit packets, which is regarded to be especially error-prone to these environments.…”
Section: Efficient Ccn Packet Dissemination By Mpr Devicesmentioning
confidence: 99%
“…Therefore, routing protocols for NAN-based WMN must have sufficient capabilities to support QoS routing and the different requirements of target applications. In [11], a performance evaluation and comparison of OLSR and the WMN standard Protocol the HWMP in ns-3 are presented. This paper was used to highlight the use of the OLSR routing protocol in NAN.…”
Section: Routing In Wmn-based Nanmentioning
confidence: 99%
“…This was achieved by presenting a case study to show the application traffic best supported by a link metric type and a demonstration of how the AHP algorithm (Equations (3), (5) and (7)) can be used to map paths calculated by a link metric to an application traffic type. The improvement of this article compared with [11,12] is that this article presents an implementation of the AHP in ns-2 using a simulation topology that represents a worst case scenario of AMI activities (where all smart meter nodes are transmitting four different application traffic types simultaneously to a data concentrator) in a five by five grid size NAN-based WMN. Equations (3), (5) and (7) are a demonstration of how the AHP is calculated, and they reference the proposed methodology presented in the second conference paper.…”
Section: Routing In Wmn-based Nanmentioning
confidence: 99%
“…Their results showed that the combination of Wi-Fi and LTE can improve control channel and random access channel performance at the cost of tolerable latency degradation. Researchers in [36] further propose the OLSR protocol to route traffic between the nodes in a smart grid.…”
Section: Related Work On Data Communicationsmentioning
confidence: 99%